"Just Antimicrobial is not Enough" Revisited—From Antimicrobial Polymers to Microstructured Dual‐Functional Surfaces, Self‐Regenerating Polymer Surfaces, and Polymer Materials with Switchable Bioactivity. Issue 19 (30th August 2022) - Zober, Maria; Lienkamp, Karen
Abstract: Biofilm formation can be slowed down by restricting protein adhesion on a surface, or by antimicrobial/biocidal activity of the material (among other methods). In this progress report, the recent work on alternatives to single component antimicrobial or protein‐repellent polymer materials is presented. These are microstructured bifunctional polymer surfaces and self‐regenerating polymer multilayer stacks. The microstructured polymer surfaces consist of antimicrobial, protein‐adhesive polymer patches, and nonfouling, protein repellent‐polymer patches. By carefully balancing the size and architecture of the adhesive and repellent patches, materials with simultaneous antimicrobial activity and strong protein repellency are obtained. At similar polymer patch sizes, protein adhesion is lower on hydrogels with a low elastic modulus than on polymer monolayers attached to stiff substrates. Surface‐regenerating polymer multilayer stacks are constructed from alternating layers of antimicrobial polymer hydrogels and degradable, soluble, or depolymerizable sacrificial layers. Top layer shedding, which imitates reptiles shedding their skin, rejuvenates the surface, and regenerates the antimicrobial function of the material. Layer shedding form such materials in solution is a competition between two thermodynamic minima, top layer reattachment and top layer removal. The outcome of each shedding event depends on the kinetics of the sacrificial layer disintegration. Abstract : In this progress report, recent work on microstructured and self‐regenerating antimicrobial polymer surfaces based on poly(oxonorbornene) is presented.